Efficiency of traditional medicine for the treatment of susto in the communities of the southern area of ​​Puno, 2023 - Calderon-Torres, Alfredo (2023)
Susto is a form of fear that occurs in all people, producing an emotional imbalance. This phenomenon is acquired in sacred and enchanted places, and in twilight hours, which generally affects the intellectual performance and routine activity of people. The purpose of this research was to examine the efficiency of traditional medicine for the treatment of susto in the communities of the southern area of Puno. The research is qualitative-inductive, descriptive-ethnographic; The in-depth interview was used as an instrument; For the analysis and interpretation of the findings, Atlas TI software was used for the analysis. The results considered the diagnosis of susto, carried out with the analysis of the reading of coca by the yatiris, to determine the patient's condition, an X-ray of the guinea pig (cavia porcellus) was used, associated with symptoms of natural and supernatural susto; For the forms of treatment, the procedure was carried out with the intervention of animals, birds, plants and minerals. The ritual practices are carried out by the yatiris, who participate with prayers, the use of offerings, clothing and a bell pronouncing the name of the patient to call the spirit and reduce the psychosocial state of the sick person with fright.